Формування основ професіоналізму майбутніх медичних сестер у процесі фахової підготовки - Закусилова, Тетяна Олександрівна; Zakusylova, T. O. (Запорізький класичний приватний ун-т, 2018)
У роботі проаналізовано вітчизняний і зарубіжний досвід формування професіоналізму майбутніх медичних сестер; окреслено суперечності, що гальмують цей процес. З’ясовано сутність понять «професіоналізм», «професіоналізм медичної сестри». Розроблено критерії сформованості компонентів професіоналізму медичної сестри: мотиваційно-ціннісного; когнітивно-професійного; операційно-діяльнісного; результативно-рефлексивного. Доведено, що підвищенню ефективності процесу формування основ професіоналізму майбутніх медичних сестер у процесі фахової підготовки сприяють організаційно-педагогічні умови: модернізація освітнього середовища шляхом його адаптації до сучасних вимог до фахової діяльності медичної сестри згідно зі світовими стандартами; оновлення підготовки майбутніх медичних сестер через впровадження інноваційних освітніх технологій та інтерактивних методів навчання; вдосконалення педагогічної майстерності викладачів-клініцистів медичного коледжу засобами науково-методичної роботи; активізація формування практичних умінь та навичок медичних сестер через імітаційне моделювання у квазіпрофесійній діяльності. Розроблено модель формування професіоналізму майбутніх медичних сестер у процесі фахової підготовки, яка включає етапи: мотиваційно-адаптаційний, освітньо-формувальний, організаційно-діяльнісний, професійно спрямований. The research highlights the conceptual foundations for the formation of the future nurses’ professionalism, outlines the role of this profession in the context of the historical development of mankind. The contradictions that slow down the process of training nurses are revealed: between the social expectations of highly skilled, competent, tolerant nurses and the lack of developed pedagogical technologies for the formation of the basis of the future nursing professionals’ professionalism; between the future nurses’ personal awareness of the necessity of the professional self-improvement, increasing the professional level and the lack of essential measures for the activation of these processes in the pedagogical theory. The national and foreign experience of medical education and the current state of the future nursing specialists’ professional training in Ukraine, European countries, USA, Canada are analyzed. The problems and perspectives about solving the problem of the forming the future nurses’ professionalism are determined. The essential characteristics of the concepts of «professionalism», «nurse’s professionalism» are analyzed. The principles and approaches that ensure the integrity of the process of forming the basis of future nurses’ professionalism are defined. The essence and the structural components of the nurse’s professionalism clarified. In the research the professional nurse's professionalism is realized as the integrative feature that combines a high level of professional competence and the technique of nursing procedures and manipulations in all areas of medicine, culture of communication, responsibility, reliability, tolerance, empathy; nursing skills; the ability to navigate and make decisions in extreme clinical situations. The criteria for the development of the components of professional nursing skills are developed: motivational-valuable; cognitive-professional operative-activity; effectively reflexive. It is proved that certain organizational and pedagogical conditions promote the increase the effectiveness of the process of forming the basis of the future nurses’ professionalism during the professional training. Among them are: modernization of the educational environment by its adaptation to the modern requirements for the professional activity of a nurse according to world standards; creation of professionally oriented educational environment by adapting it to the specifics of the nurse’s professional activity; improvement the pedagogical skills of the clinical teachers of medical college by means of scientific and methodical work; activation the process of forming nurses’ practical skills through the simulation in quasi-professional activity.
Formation of the basis of the future nurses’ professionalism in the process of the professional training.
Keywords: інтерактивні методи; компетентність; майбутня медична сестра; організаційно-педагогічні умови; професіоналізм; фахова підготовка; interactive methods; competence; future medical nurse; organizational and pedagogical conditions; professionalism; professional training